Passive parametric modeling of dynamic loudspeakers. - Franken, D.
In this paper, an electrical circuit is proposed which is suitable for a parametric modeling of electrodynamic transducers, e.g., dynamic loudspeakers. Since the system modeled is known to be passive, the preservation of this property is a key issue of the approach presented here. This is of special importance when nonlinear effects are taken into account, as passivity always ensures different kinds of stability. The only nonlinear elements occurring in the circuit model are ideal transformers, the turns ratios of which are not constant but depend, in particular, on some signal quantity. As a consequence, the circuit can be digitally simulated by applying principles known from the theory of wave digital filters
Keywords: Bass loudspeaker; Car radio; Digital simulation; Dynamic loudspeakers; Electrical circuit; Electro-dynamic transducers; Ideal transformers; Nonlinear effects; Nonlinear elements; Passive parametric modeling; Passivity; Stability